Doble Filiación Parental análisis jurídico, doctrinario y comparativo de la Sentencia N.o 184-18-SEP-CC. - Reyna Martínez, Nemesis Eilyn (2024)
The present work of curricular integration titled as “ Double parental filiation; legal, doctrinal and comparative analysis of the judgement N° 184-18-SEP.CC”, was developed with the purpose of analyzing the double filiation fatherly or motherly figure recognized for the first time in the country with the judgement, which is also object of study, the legal importance of this case in the recognition and extension of rights regarding the LGBTI community to recognize their paternity and maternity to a legal level, but overall, the considerations and criteria made by the judges of the Court about the violated rights of the girl Satya and the Principle of children ́s best Interest. In the frame for the elaboration of the present work various research materials, such as digital and physical bibliographical sources, judgements issued by the Constitutional Court and by judicial entities of other countries, and national and compared legislation, were collected. The employed methods were: analytic, inductive-deductive and historical-logical. This investigation was also complemented with the study of cases carried out for the development of the work. The mentioned background permitted to evidence that it was not made a correct consideration and application of the constitutional rules, resulting on the part of administrative authorities of the Civil Registration in the violation of rights of a child, making the infra-constitutional rule prevail. Hence, the considered criteria in the judgment permitted an advance in the ambit of children and teenagers’ rights and about the double filiation. For this reason and considering what was ruled in the judgment, it is also possible to suggest the adequation of the regulation regarding the adjustment of this figure in the Civil Code and the Organic Law of Management and Civil Data.